A preliminary review of the proposed single currency zone in the CARICOM region - Williams, Gladwin B. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Analyzes some of the major issues which will confront the CARICOM region as it seeks to establish a single currency.